Circumpolar contamination in eggs of the high‐arctic ivory gull Pagophila eburnea. (5th May 2015) - Lucia, Magali; Verboven, Nanette; Strøm, Hallvard; Miljeteig, Cecilie; Gavrilo, Maria V.; Braune, Birgit M.; Boertmann, David; Gabrielsen, Geir W.
Abstract The ivory gull Pagophila eburnea is a high‐Arctic species threatened by climate change and contaminants. The objective of the present study was to assess spatial variation of contaminant levels (organochlorines [OCs], brominated flame retardants [BFRs], perfluorinated alkyl substances [PFASs], and mercury [Hg]) in ivory gulls breeding in different areas across the Arctic region as a baseline for potential future changes associated with climate change. Contaminants were already determined in eggs from Canada (Seymour Island; except PFASs), Svalbard in Norway (Svenskøya), and 3 sites in Russia (Nagurskoe, Cape Klyuv, and Domashny). New data from Greenland allowed the investigation of a possible longitudinal gradient of contamination. The most quantitatively abundant OCs were p, p′‐dichlorodiphenyldichloroethylene (DDE) and polychlorobiphenyls. Mercury concentrations were higher in Canada compared with other colonies. Eggs from Nagurskoe often were characterized by higher OC and BFR concentrations. Concentrations gradually decreased in colonies situated east of Nagurskoe. In contrast, PFAS concentrations, especially perfluorooctanoate and perfluorononanoate, were higher in Greenland. Some of the contaminants, especially Hg and p, p′‐DDE, exceeded published thresholds known to disrupt the reproductive success of avian species. Overall, the levels of OCs, BFRs, and PFASs did not suggest direct lethal exposure to these compounds, but their potential synergetic/additive sublethal effects warrant monitoring. Environ Toxicol Chem 2015;34:1552–1561. © 2015 SETAC